2021
DOI: 10.3390/v13030469
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of PEDV-Carrying CD3+ T Cells Migrate into the Intestinal Mucosa of Neonatal Piglets

Abstract: Porcine epidemic diarrhea virus (PEDV) can cause intestinal infection in neonatal piglets through the nasal cavity. A process in which CD3+ T cells carry PEDV plays a key role. However, the modes through which PEDV bridles CD3+ T cells as a vehicle for migration to the intestinal epithelium have not been clarified. In this study, we first demonstrated that PEDV could survive in blood-derived CD3+ T cells for several hours, depending on the multiplicity of infection. In addition, PEDV preferentially survived in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Integrin αvβ3 enhances PEDV replication in Vero E6 and porcine intestinal epithelial cells [ 30 ]. Chen et al reported that the PEDV virus was transferred to intestinal epithelial cells via cell-to-cell contact by blood-derived CD3+ T cells in neonatal piglets via blood circulation following an increase in gut-homing integrin α4β7 [ 31 ]. The results illustrate that integrins α3 and β are involved in PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin αvβ3 enhances PEDV replication in Vero E6 and porcine intestinal epithelial cells [ 30 ]. Chen et al reported that the PEDV virus was transferred to intestinal epithelial cells via cell-to-cell contact by blood-derived CD3+ T cells in neonatal piglets via blood circulation following an increase in gut-homing integrin α4β7 [ 31 ]. The results illustrate that integrins α3 and β are involved in PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the relationship between PEDV infection and T cells has been described, which is mainly characterized by poor effector cytotoxic activity (Yuan et al, 2021). The knowledge of the role of B cells has been primarily focused on antibody secretion during PEDV infection (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%